Highly Prevalent Multidrug-Resistant Salmonella From Chicken and Pork Meat at Retail Markets in Guangdong, China - Zhang, Lina; Fu, Ying; Xiong, Zhiying; Ma, Yeben; Wei, Yihuan; Qu, Xiaoyun; Zhang, Hongxia; Zhang, Jianmin; Liao, Ming (Frontiers in Microbiology, 2018)
This study aimed to investigate the prevalence, serotype distribution, and antibiotic resistance, and to characterize the extended spectrum β-lactamases (ESBLs) producing Salmonella isolates from chicken and pork meats from retail markets in Guangdong province, China. A total of 903 retail meat samples (475 chicken and 428 pork meats) were obtained from six cities (Guangzhou, Shenzhen, Heyuan, Shaoguan, Foshan, and Yunfu) of Guangdong province between May 2016 and April 2017. High levels of Salmonella contamination were detected in chicken (302/475, 63.6%) and pork (313/428, 73.1%). Thirty-eight serotypes were identified in 615 detected Salmonella, and the serotypes varied greatly between chicken and pork samples. Agona (55/302, 18.2%), Corvallis (45/302, 14.9%), Kentucky (38/302, 12.6%), Mbandaka (32/302, 10.6%) was the dominant serotypes in chicken samples. However, Typhimurium (78/313, 24.9%), Rissen (67/313, 24.1%), Derby (66/313, 21.1%), and London (48, 15.3%) were the most common in pork samples. High rates of antibiotic resistance were found to sulfisoxazole (468/615, 76.1%), tetracycline (463/615, 75.3%), ampicillin (295/615, 48.0%), and ofloxacin (275/615, 44.7%). Notably, antimicrobial susceptibility tests identified resistance to polymyxin B (12/615, 2.0%) and imipenem (3/615, 0.5%). Multidrug-resistance (MDR) was detected in Salmonella isolated from chicken (245/302, 81.1%) and pork (229/313, 73.2%). The resistance rate of different Salmonella serotypes varied widely. Especially, isolates such as Typhimurium, Agona, Corvallis and Kentucky exhibited highly resistance to antibiotics. The MDR rate of Salmonella isolates from chicken was significantly higher than that from pork isolates (P < 0.05). Twenty-one Salmonella isolates were identified as ESBLs-producing, covering six Salmonella serotypes and displaying different pulse field gel electrophoresis (PFGE) genotypes. BlaOXA-1 was the dominant ESBLs gene (9/21, 42.9%), followed by blaCTX-M-55 (5/21, 23.8%). This study indicated that Salmonella was widespread in chicken and pork from retail markets in Guangdong province and the isolates showed high multidrug-resistance, especially the known multidrug-resistant Salmonella serotypes. Therefore, it is important to focus on Salmonella serotypes and strengthen the long-term monitoring of MDR Salmonella serotypes in animal-derived foods.